PENGARUH PROYEK PENGUATAN PROFIL PELAJAR PANCASILA TERHADAP KARAKTER RELIGIUS PESERTA DIDIK - Wildan Habibi; Chofifah Assajdah (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2025)
The background to this research explains the influence of the Project to strengthen the Pancasila student profile on the religious character of grade 7 students at MTsN 1 Kediri. The method used by researchers in this research is a quantitative method with the Expost facto type, namely research with the aim of finding causes that allow changes in symptoms or behavioral phenomena caused by independent variables. The population in this study was taken from all 7th grade students at MTsN 1 Kediri and the sample was taken using simple random sampling or a total of 123 students were chosen randomly. This research instrument consists of ability tests, psychology, and questionnaires for the project to strengthen students' profiles of Pancasila and religious character. The findings in this research are based on simple correlation test analysis, determination analysis test, simple regression analysis test, significance test (F), and partial test(t) which show: there is a significant influence between variable X and Y with the correlation value (r) 0.756 and coefficient of determination 0.571 or 57.1%.